Antimicrobial Effect Of Diode Laser With Curcumin Nanoparticles Against Enterococcus Faecalis. (In Vitro Study) (Journal of Pharmaceutical Negative Results, 2023)
Aim: to determine the bactericidal effect of diode laser (445 nm) and curcumin nanoparticles on Enterococcus faecalis. Methodology: Fifty extracted maxillary anterior human teeth with one root canal were inoculated with Enterococcus faecalis and organized into five groups; (I) Control group, (II) Sodium hypochlorite group, (III) Laser group, (IV) Curcumin nanoparticles group and (V) Laser with curcumin nanoparticles group. After the treatment protocol, the samples were analyzed by colony forming units (CFU) for analysis of the remaining bacteria. Also, they were stained with dyes to detect live and dead bacteria using a confocal laser scanning microscope (CLSM). Statistical analyses were performed using using ANOVA test followed by Tamahne post hoc test for pairwise comparisons. Significance level for statistical tests was set at 0.05. Statistical analysis was performed using SPSS software (IBM Corp. Released 2017. IBM SPSS Statistics for Windows, Version 25.0. Armonk, NY: IBM Corp.) Results: CFU: The control group showed the highest bacterial load followed by the CurNP group then the CurNP-L group then the laser group and finally the NaOCl group with a significant difference between them. CLSM: The CurNP-L group showed the highest bacterial percentage reduction followed by the NaOCl group then the laser group then CurNP group and finally the control group with a significant difference between them. Conclusion: Curcumin nanoparticles had an antibacterial effect on E.feacalis which could be enhanced using low power diode laser.